Equity implications for sanitation from recent health and nutrition evidence - A. A. Cronin; M. E. Gnilo; M. Odagiri; S. Wijesekera (BMC, 2017)
Abstract Recent evidence points to the possible underestimation of the health and nutrition impact of sanitation. Community sanitation coverage may first need to reach thresholds in the order of 60% or higher, to optimize health and nutrition gains. Increasing coverage of sanitation to levels below 60% of community coverage may not result in substantial gains. For example, moving Indonesia from 60% to 100% improved sanitation coverage could significantly reduce diarrhoea in children under 5 years old (by an estimated 24% reduction in odds ratio for child diarrhoea morbidity) with gains split equally by reaching underserved communities and the unserved within communities. We review the implications of these results across three levels of program implementation - from micro level approaches (that support communities to achieve open defecation-free status), to meso level (sub-national implementation) to macro level approaches for the national enabling environment and the global push to the Sustainable Development Goals. We found significant equity implications and recommend that future studies focus more extensively on community coverage levels and verified community open defecation free status rather than household access alone. Sanitation practitioners may consider developing phased approaches to improving water, sanitation and hygiene in communities while prioritizing the unserved or underserved.